2007
DOI: 10.1111/j.1468-2982.2007.01416.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Cerebral Venous Thrombosis in a Patient With Spontaneous Intracranial Hypotension

Abstract: Spontaneous intracranial hypotension (IH) may indicate cerebrospinal fluid (CSF) leakage, in the absence of a known dural puncture or tear. Intracranial vascular complications of spontaneous IH include subdural haematoma (SDH), subdural effusion (SDE) and, rarely, cerebral venous thrombosis (CVT) (1-3) and dural arteriovenous fistula (AVF) (3). In this report, we describe a patient with spontaneous IH who unusually developed all of these intracranial vascular complications. It is noteworthy that CVT occurred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
2
15
0
1
Order By: Relevance
“…16 Conversely, a French study of 62 adults with isolated lateral sinus thrombosis found that only 3 cases were related to parameningeal infections. 42 Other conditions have been associated with CVT in case reports or small series, including paroxysmal nocturnal hemoglobinuria, 48 iron deficiency anemia, 49 thrombocythemia, 50 heparin-induced thrombocytopenia, 61 thrombotic thrombocytopenic purpura, 14 nephrotic syndrome, 51 inflammatory bowel disease, 10,62 systemic lupus erythematosus, 52 Behçcet disease, 53 mechanical precipitants, epidural blood patch, 45 spontaneous intracranial hypotension, 46 and lumbar puncture. 47 …”
Section: Other Uncommon Causesmentioning
confidence: 99%
“…16 Conversely, a French study of 62 adults with isolated lateral sinus thrombosis found that only 3 cases were related to parameningeal infections. 42 Other conditions have been associated with CVT in case reports or small series, including paroxysmal nocturnal hemoglobinuria, 48 iron deficiency anemia, 49 thrombocythemia, 50 heparin-induced thrombocytopenia, 61 thrombotic thrombocytopenic purpura, 14 nephrotic syndrome, 51 inflammatory bowel disease, 10,62 systemic lupus erythematosus, 52 Behçcet disease, 53 mechanical precipitants, epidural blood patch, 45 spontaneous intracranial hypotension, 46 and lumbar puncture. 47 …”
Section: Other Uncommon Causesmentioning
confidence: 99%
“…It well established that both CVST and SDH can arise as a secondary complication of intracranial hypotension. [681215222324252930]…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that intracranial hypotension can cause SDH due to sagging brain structures and venous engorgement. [681215222324252930] The secondary cerebral venous engorgement due to the low ICP [22] and associated stasis [30] can lead to secondary CVST. Orthostatic headaches should increase concern for intracranial hypotension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, anticoagulation treatment had yielded full improvement in the following course. In the literature, there is considerable evidence supporting the occurrence of CVT as a consequence of ICH (2,3,4,5); hence, treatment of solely ICH, as the inducer agent, was generally recommended (6). In a retrospective review by Schievink and Maya (2), ICH was indicated as a risk factor for CVT; however, there was no evidence for CVT preceeding ICH in any patient.…”
mentioning
confidence: 99%